Study of Student Motivation on English Learning IN SMUN 1 Teminabuan, Sorong, West Papua - Ida Siti Hamidah (Syntax Idea)
This study aims to investigate factors that affect the level of student motivation in English subjects. Researcher describe the same conditions that have occurred in the Teminabuan district, West Papua. In this area, students experience difficulties in learning English, especially in communication or conversation. Researcher used qualitative research methods, because they fit perfectly with the problem under study. Researcher conducted interviews with students, and English teachers at SMUN 1Teminabuan. Research data in this study used an interview that was questioned to respondents to be answered in order to get valid answers . In addition, researchers also monitor student learning methods and learning systems to measure students' abilities in learning English. The instruments used were 20 questions that had been provided. Analyst data obtained by means of qualitative descriptive techniques in the form of descriptions of phenomena that occur in the Teminabuan district. The results showed that the intrinsic and extrinsic factors were very influential on student learning motivation. Based on this research, it can be concluded that negative behavior can reduce student learning motivation, and positive behavior and increase student learning motivation.